Hubungan Pengetahuan dan Sikap Perawat terhadap Pelaksanaan Keselamatan Pasien di RSU Baitul Hikmah Kendal - Indah Djubaedah; Sri Wahyuni; Apriliani Yulianti (STIKes Ibnu Sina Ajibarang, 2025)
Patient safety is a critical component of healthcare services, particularly as it directly impacts patient outcomes and the quality of hospital care. Nurses, as the frontline health professionals, play an essential role in implementing patient safety standards. This study aimed to analyze the relationship between nurses’ knowledge and attitudes toward the implementation of patient safety at Baitul Hikmah General Hospital Kendal. A descriptive correlational design with a cross-sectional approach was employed. The study recruited 78 nurses using a total sampling technique, and data were collected through questionnaires that had been previously tested for validity and reliability. The results indicated that the majority of nurses demonstrated good levels of knowledge and attitudes, which were reflected in their adherence to patient safety practices. Bivariate analysis using the Spearman Rho test revealed a significant relationship between nurses’ knowledge (p-value = 0.008; r = 1.000) and attitudes (p-value = 0.008; r = 0.297) with the implementation of patient safety. These findings suggest that better knowledge and positive attitudes among nurses significantly contribute to the proper implementation of patient safety protocols. Consequently, continuous education, training, and awareness programs are necessary to strengthen nurses’ knowledge and attitudes, thereby improving the quality of healthcare services and minimizing risks to patient safety in hospital settings.